Potential of Mangrove Ecosystem for Silvofishery Development in Kutai National Park, East Kalimantan - Iin Sumbada S, Erny P, Muli E, Imanuddin . (Universitas 17 Agustus 1945 Samarinda, 2017)
Silvofishery is one of effort of area exploiting with conservation principle. This research to predict potency of mangrove ecosystem which can support to silvofishery development inside conservation area. This study aims to examine the mangrove ecosystems potential for silvofishery, by knowing the vegetation structure, density and diversity of plankton, nekton, dissolved oxygen, temperature, salinity and mud thickness. The research was conducted in Teluk Lombok, Teluk Kaba and Muara Teluk Pandan. The method used is multiple plot method with random purposive sampling system. The results showed that the mangrove vegetation density in Teluk Lombok was 3.116.7 plants ha-1, Teluk Kaba 2,966.7 plants ha-1 and Muara Teluk Pandan 2,416.7 plants ha-1. Nekton density in the Teluk Lombok is 5.38 individual m-2, Teluk Kaba 8.21 individual m-2 and Muara Teluk Pandan 7.13 individual m-2. There are 40 species of plankton in Teluk Lombok with density 4.565,3 individual per liter, in Muara Teluk Pandan 21 species of plankton density 2,946,5 individual per liter, then Teluk Kaba 24 species of plankton and density 3,029,5 individual per liter. For all three locations there are four parameters that do not support for silvofishery, namely are density of plankton, dissolved oxygen, pH and salinity. Then there are four parameters supporting for silvofishery, ie vegetation density, nekton density, temperature, and mud thickness.